(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. A few data on the prevalence of renal involvement in cystic fibrosis and its spectrum in childhood is available. In the present study, we conducted a prospective study on children who had cystic fibrosis and evaluated their renal involvement. In fact, the aim of the study was to provide data on the clinical consequences of proper identification of kidney disease in a group of children with cystic fibrosis. Methods. This prospective study was conducted on 55 consecutive patients with previous diagnosis of cystic fibrosis during a threeyear period and at least 3 months to over 5 years or more follow-up. The inclusion criteria was the diagnosis of cystic fibrosis which was made by clinical presentation of cystic fibrosis and laboratory results. Initially, patients’ medical records were reviewed and relevant data were collected. A 24-hour urine collection (or a random urine sampling in very young infants) was used to assess crystalluria and renal function was evaluated by blood sampling. Results. Totally, 55 patients with cystic fibrosis were admitted in two hospitals with the mean age of 8.22 ± 5.66 years. GFR totally reduced in 34.5%. The overall prevalence of hypercalciuria was estimated to be 60%, while hyperoxaluria, hypocitraturia, and hyperuricosuria in 41.8%, 24.5%, and 47.3%; respectively. Conclusion. Crystalluria is a common consequence of cystic fibrosis in childhood. The prevailing crystalluric finding includes hypercalciuria followed by hyperuricosuria, and hyperoxaluria. During disease GFR may be decreased due to several reasons such as nephrotoxic drugs usage.